2007
DOI: 10.1111/j.1365-313x.2007.03223.x
|View full text |Cite
|
Sign up to set email alerts
|

AtDUR3 represents the major transporter for high‐affinity urea transport across the plasma membrane of nitrogen‐deficient Arabidopsis roots

Abstract: SummaryDespite the fact that urea is a ubiquitous nitrogen source in soils and the most widespread form of nitrogen fertilizer used in agricultural plant production, membrane transporters that might contribute to the uptake of urea in plant roots have so far been characterized only in heterologous systems. Two T-DNA insertion lines, atdur3-1 and atdur3-3, that showed impaired growth on urea as a sole nitrogen source were used to investigate a role of the H + /urea co-transporter AtDUR3 in nitrogen nutrition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 64 publications
(129 reference statements)
9
117
1
Order By: Relevance
“…Concerning urea, molecular analysis of AtDUR3 expression showed that its expression is downregulated by NO 3 − and NH 4 + , but markedly induced by supply of urea (Fig. 3, Kojima et al 2007). Yet no further progress had been done to delineate this complex regulation.…”
Section: Regulatory Mechanisms Affecting Root N Uptake Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…Concerning urea, molecular analysis of AtDUR3 expression showed that its expression is downregulated by NO 3 − and NH 4 + , but markedly induced by supply of urea (Fig. 3, Kojima et al 2007). Yet no further progress had been done to delineate this complex regulation.…”
Section: Regulatory Mechanisms Affecting Root N Uptake Systemsmentioning
confidence: 98%
“…A. thaliana plants possess a high-affinity urea transporter (DUR3, Fig. 1) that is involved in taking up environmental urea but may also mediate internal urea transport (Liu et al 2003a;Kojima et al 2007). DUR3 was identified by its similarity to the urea transporter of Saccharomyces cerevisiae (ScDUR3), and was shown to account for most of the root urea HATS activity ).…”
Section: Organic N Transportersmentioning
confidence: 99%
“…8 On the other hand, the effect of nitrate to limit urea uptake was sustained by a down regulation of urea transporter DUR3 when inorganic N source, nitrate or ammonium nitrate, were supplied along with urea. 8,39,42 Further transcriptional changes of the assimilation pathways were identified when both sources were applied in the external solution. Microarray data in Arabidopsis and maize, revealed that urea and nitrate treatment in comparison to nitrate alone increased the up-regulation of nitrate-responsive genes, in particular of those involved in the uptake and assimilation of nitrate.…”
Section: Physiological and Transcriptional Changes Occurring Under Urmentioning
confidence: 99%
“…It is well known that urea is absorbed as an intact molecule by plant leaves and roots [116] by means of specific root transporters [117,118]. Although the use of urea is mainly as a source of N fertilizer, the contribution of plant urea uptake and metabolism in a physiological and agricultural context is still not investigated.…”
Section: Nitrogen Assimilation By Plantsmentioning
confidence: 99%